2018
DOI: 10.1155/2018/6972848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partial Replacement of Pork Meat with Chicken or Duck Meat on the Texture, Flavor, and Consumer Acceptance of Sausage

Abstract: This study investigated the textural and sensory characteristics of sausage, where pork meat was partially replaced with chicken or duck meat (5-30% replacement). Nine treatments including the control (100% pork) were used in this study. TPA showed hardness to be decreasing as larger proportions of chicken or duck meat were substituted for pork meat. Descriptive analysis revealed that greater amounts of chicken or duck meat produced lower intensities of hardness, springiness, and chewiness and tended to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Chicken meat and its by-products are among the first-choice foods in most countries, due to the health benefits they provide [ 2 ] and the relatively low price [ 3 ]. According to the National Chicken Council, the price of chicken is about 2 or 3 times lower, than that of beef or pork.…”
Section: Introductionmentioning
confidence: 99%
“…Chicken meat and its by-products are among the first-choice foods in most countries, due to the health benefits they provide [ 2 ] and the relatively low price [ 3 ]. According to the National Chicken Council, the price of chicken is about 2 or 3 times lower, than that of beef or pork.…”
Section: Introductionmentioning
confidence: 99%
“…Texture is important to overall acceptance of meat products by consumers (Lee et al , ), and their preference in meat products texture varies, for example older consumers might prefer a softer texture that facilitates chewing and swallowing. Roininen et al () showed that older adults preferred foods that can be consumed effortlessly providing an easy eating experience, but at the same time, textures that were too smooth or too soft were not appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…These evaluations were studied simultaneously, because the relationship between the “meat odor/flavor” and the “metallic taste” had already been established. The inverse relationship between these attributes can be given, because chicken is meat, and although it is not fatty, it can increase the juiciness and smoothness of the dish when processed [ 41 ]. This can be augmented by the recipe of the dish, which in addition to high chicken content (56.5%) contains olive oil (1.4%) and its lubricating characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For the ChS dish, the number of correct identifications dropped to 10 ( Figure A2 e). It has become evident that chicken brings little flavor and even diminishes the existing flavor in dishes where it is added [ 41 ]. This explains why a large proportion of the ingredients in its recipe was found by judges ( Figure A2 f), as in the case of “stuffed peppers”.…”
Section: Discussionmentioning
confidence: 99%